Морфологічні особливості пилкових зерен видів родини Сolchicасеае DC. флори України - Gnatiuk, A.M.; Gournenko, І.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The results of study the pollen grains оf Colchicaceae species of Ukrainian flora are presented. It was found that the pollen grains of Colchicum autumnale L., C. fominii Bordz., C. umbrosum Steven, Bulbocodium versicolor (Ker.-Gawl.) Spreng are the same type. They have grains of elongated ellipsoidal shape with two pores. C. ancyrense B.L. Burtt grains differ in shape and number of pores. It has grains oblate spherical with four or more pores.